Focus shifts to behaviors (Getting Results ... for the Hands - On Manager, 1995)
One of the hottest corporate management subjects today is competency modeling - an attempt to determine the knowledge, skills, abilities, and even traits and motivations critical to achieving strategic objectives. Some businesses are using competency modeling to identify the baseline or minimum requirements in any functional area or job, but most organizations are using the technique to identify what makes a superperformer. As part of the process, exemplary performers are interviewed to determine what characteristics are behind their success. Then average performers are interviewed, and the data are compared.